2016
DOI: 10.1155/2016/4062579
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Rescues Synaptogenesis Impairment and Long-Term Memory Deficits Caused by Postnatal Multiple Sevoflurane Exposures

Abstract: Sevoflurane exposures were demonstrated to induce neurotoxicity in the developing brain in both human and animal studies. However, there is no effective approach to reverse it. The present study aimed to evaluate the feasibility of utilizing docosahexaenoic acid (DHA) to prevent sevoflurane-induced neurotoxicity. P6 (postnatal 6 days) mice were administrated DHA after exposure to 3% sevoflurane for two hours daily in three consecutive days. Molecular expressions of synaptic makers (PSD95, synaptophysin) and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…At this age point, it is not so clear that the pathology would provoke significant alteration of synaptic markers, so the effect observed should be only related to the dietary effect. DHA has been described to increase synaptic proteins such as synaptophysin and PSD95 [77]. Our results showed no evident modifications of the analyzed proteins, although the levels of phospho-synapsin were strongly affected by lower dietary ω-6/ω-3 ratio in females [29,34].…”
Section: Discussioncontrasting
confidence: 47%
“…At this age point, it is not so clear that the pathology would provoke significant alteration of synaptic markers, so the effect observed should be only related to the dietary effect. DHA has been described to increase synaptic proteins such as synaptophysin and PSD95 [77]. Our results showed no evident modifications of the analyzed proteins, although the levels of phospho-synapsin were strongly affected by lower dietary ω-6/ω-3 ratio in females [29,34].…”
Section: Discussioncontrasting
confidence: 47%
“…Normal expression of JunB has been shown to be essential to genetic stability, and is implicated in cell survival, cell proliferation, and programmed cell death and senescence [33]. Research has shown that exposure to sevoflurane results in decreased synaptic density, filopodia length, neuronal spines, and spine density of apical dendrites [12,43,44]. Inappropriate transcription of junB and arc may underlie dysregulated synaptic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to the inhalational anesthetic sevoflurane during critical stages of brain development induces widespread neuronal apoptosis in various mammalian species [6][7][8][9]. Sevoflurane-induced neurotoxicity and synaptic morphological changes are associated with behavioral deficits exhibited as juveniles and adults [10][11][12]. Importantly, cognitive deficits have been reported in unexposed offspring of dams exposed in utero, suggesting that exposure to anesthetics may result in a transgenerational epigenetic modifications [13].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, sevoflurane has been shown to induce cellular apoptosis [813], endoplasmic reticulum stress [9, 1416], synaptogenesis impairment [1720], mitochondrial dysfunction [18, 20] and neuroinflammation [9, 21] in vitro and in vivo in mice. These effects may then lead to cognitive impairment in young mice [22].…”
Section: Introductionmentioning
confidence: 99%